Music for cleansing the universe-drumming and gong ensemble music in the Mamahui Pogun ceremonies of the Lotud Dusun of Tuaran, Sabah, Malaysia - Jacqueline Pugh-Kitingan; Judeth John Baptist (Borneo Research Council, Inc, 2009)
Mamahui Pogun is a major cycle of rituals performed over several weeks during times of calamity, among all the villages of the Lotud Dusun of Sabah, the east Malaysian state of northern Borneo. The Lotud speak one of the more than 50 Austronesian languages spoken by the main part of the population of Sabah (King and King 1984). They number around 10,000, and live mainly in the Tuaran District and Tamparuli Sub-District on the west coast of Sabah. The Lotud language is a member of the indigenous Dusunic Family of Languages, which consists of around 13 languages including Kadazandusun, the largest overall language in the state in terms of numbers of speakers (Banker and Banker 1984, Blood 1990:63, Johansson 2004). Most Lotud are also fluent in the languages of neighboring peoples, such as the Kadazandusun, and west coast Bajau, and also the national language, Bahasa Malaysia. Over the centuries, they have also had extensive contacts with the Iranun and the Brunei. The Lotud identify themselves as Lotud and recognize their differences from other cultural groups. In addition to their language, other distinguishing cultural features include a distinctive costume worn by older women, music traditions, belief system and ritual practices.